Characteristics of Victims in Child Sexual Abuse Cases in Southern Provinces and Cities of Vietnam and Prevention Solutions - Thieu, Le Van (2019)
The right to protection of human life, health, dignity and honor is the sacred and noble right, recognized in the Constitution and protected by the Vietnamese Criminal law. However, in the pass years, the situation of crimes of sexual assault including child sexual abuse in Southern provinces and cities which are 32 provinces and cities from Da Nang to Ca Mau has been complicated both in number and nature of activities. In this paper, the author intends to investigate the criminal situation, characteristics of victims in child sexual abuse cases, legal framework of prevention measures, as well as some recommendations for Vietnam